Apache Kafka series : learn Apache Kafka for beginners - Maarek, Stéphane (Packt Publishing, 2018)
"Apache Kafka has become the leading data-streaming enterprise technology. Kafka is used in production by over 2000 companies like Netflix, Airbnb, Uber and LinkedIn. To learn Kafka easily, step-by-step, you have come to the right place! Apache Kafka and its ecosystem: In this section, we will learn about the Apache Kafka ecosystem, and see how some target architectures may look. This high-level section helps you to set context around Kafka! Apache Kafka Core concepts: In this section, we will learn about all the fundamental concepts of Kafka like topics, partitions, replication, brokers, producers, consumers, consumer groups, Zookeeper, delivery semantics, and more! Docker and Kafka Setup: In this section, we will learn how to install Docker on your machine and get started with Apache Kafka, in the simplest way possible. Apache Kafka Hands-on Practice: In this section, we will gain some practical experience by learning how the various command lines tool work, as well as how to use the Kafka Topics UI, and create your very first producer and consumer in Java. Code Examples - Libraries Integrations: In this section, we will learn about some more advanced code examples, and understand where to find the libraries to integrate with frameworks such as Spark, Spark Streaming, Akka Streams, Scala, Actors, Apache NiFi. Advanced Topic Configuration: In this section, we will understand the main configurations for your topics, learn about log compaction, and understand exactly what your partitions are made of!"--Resource description page